Mining hidden information from library databases using SOM (Self Organizing Map) - Md. Sap, Mohd. Noor; Defit, Sarjon (2001)
The proliferation of textual and multimedia databases, digital libraries, internet servers and intranet services has increased rapidly. It has turned researchers' and practitioners' dream of creating an information rich society into a nightmare of information gluts. Powerful methods are needed for the extraction of miscellaneous document collections. The Websom, information retrieval based on SOM, method organizes a document collection on a map display that provides an overview of the collection and facilitates interactive browsing. The potential of the Websom method has been tested where article from Usenet Newsgroups have been organized. Our study concludes that interesting documents can be retrieved by a content addressable search of interesting map locations. The interesting location should be marked as filters for collecting interesting new documents.